An Analysis of Lexical Cohesion in Rubric Opinion of The Jakarta Post Published in May 2013 - Marwan Febri (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
This research was conducted by Marwan Febri, NIM. 209 3235 72, entitled “An Analysis of Lexical Cohesion in Rubric Opinion of The Jakarta Post Published in May 2013”. The purpose of this research was to investigate the lexical cohesion’s division and their analysis based on the contexts. The method of this research was descriptive qualitative method. The object of this research was rubric opinion of The Jakarta Post published in May 2013 which were taken seven opinions. The result showed that there were four lexical cohesion’s division found in the texts such as : reiterating with the same word, reiterating by synonym, superordinate, and antonym. They were shared in the texts randomly. 50 words were reiterated with the same word. Reiterating with synonym were 4. Hypernym words were 21. There were 12 antonym words from all texts